Carcass Weight and Skeletal Muscle Microscopic Structure of Red Nile Tilapia (Oreochromis niloticus) in The Different Aeration and Filtration - Muhammad Anwar Djaelani; Kusuma Alya Fathurika; Kasiyati Kasiyati; Sunarno Sunarno (Al-Kauniyah: Jurnal Biologi, 2024)
AbstractRed tilapia (Oreochromis niloticus) is a freshwater fish that widely liked by Indonesian people. Keeping fish with good water quality will increase productivity. The aim of this research was to determine the effect of adding aeration and using filters on carcass weight, muscle fiber diameter and number of muscle fibers in red tilapia. This research used 24 red tilapia fish with an initial body weight of around 7 g. Divided into 4 groups, namely the maintenance group using one aerator without a filter (ANF), the maintenance group using two aerators without a filter (AANF), the maintenance group using one aerator and using a filter (AF) and the maintenance group using two aerators and using a filter (AAF). The results showed that rearing red tilapia fish in the group rearing two aerators and using a filter had a significant effect (P <0.05) on carcass weight, muscle fiber diameter, and number of muscle fibers. Observation of the muscle histology structure showed that there was no damage to the muscle histology structure. The conclusion of this research indicate that additional aerator equipped with filters will supports the growth of red tilapia fish.AbstrakIkan nila merah (Oreochromis niloticus) merupakan ikan yang banyak disukai masyarakat Indonesia. Pemeliharaan ikan dengan kualitas air yang baik akan memberikan peningkatan produktivitas. Tujuan penelitian ini adalah mengetahui pengaruh penambahan aerasi dan penggunaan filter terhadap bobot karkas, diameter serabut otot serta jumlah serabut otot pada ikan nila merah. Penelitian ini menggunakan 24 ekor ikan nila merah dengan bobot badan awal berkisar 7 g. Dibagi menjadi 4 kelompok, yaitu kelompok pemeliharaan menggunakan satu aerator tanpa filter (ANF), kelompok pemeliharaan menggunakan dua aerator tanpa filter (AANF), kelompok pemeliharaan menggunakan satu aerator dan menggunakan filter (AF) serta kelompok pemeliharaan menggunakan dua aerator dan menggunakan filter (AAF). Hasil menunjukkan pemeliharaan ikan nila merah pada kelompok pemeliharaan dua aerator dan menggunakan filter berpengaruh nyata (P <0,05) terhadap bobot karkas, diameter serabut otot, dan jumlah serabut otot. Pada pengamatan struktur histologi otot menunjukkan tidak adanya kerusakan struktur histologi otot. Kesimpulan penelitian ini penambahan aerator dilengkapi filter mendukung pertumbuhan ikan nila merah.